Intercultural Sensitivity, L2 Motivation, and Willingness to Communicate in EFL: A Systematic Review and Meta-Analysis - Ahmad Sugianto; Sherina Gema Millennium; Rojab Siti Rodliyah; Eri Kurniawan (Abjad Journal of Humanities & Education, 2026)
This study aims to synthesise evidence on intercultural sensitivity, L2 motivation, and willingness to communicate (WTC) in English as a foreign language (EFL) contexts to examine their contributions to the social psychology of communication. A systematic literature review (SLR) combined with meta-analysis was conducted in accordance with the PRISMA guidelines. Twenty-nine studies between 2005 and 2026 were identified in the Scopus database based on predefined inclusion criteria, which encompassed English-language and open-access publications. The selected studies were analysed using thematic analysis to scrutinise the conceptual trends and meta-analysis to estimate the magnitude and direction of the relationships and intervention effects. The qualitative synthesis suggests that the dynamic interplay among psychological, social, and intercultural factors shapes communication in EFL contexts. The meta-analysis of cross-sectional studies showed a significant moderate positive relationship between L2 motivation and WTC (random-effects r=0.449, 95% CI: 0.361-0.530, p< 0.001) and a significant positive relationship between intercultural sensitivity/intercultural competence and L2 motivation (random-effects r=0.544, 95% CI:0.009-0.837, p=0.047). Meta-analyses of intervention studies report moderate-to-large positive effects of intercultural sensitivity (g=0.779, 95% CI: 0.551-1.008) and L2 motivation (g=0.495, 95% CI: 0.242-0.747). A large pooled effect was also reported for WTC (g= 2.637, 95% CI: 0.628-4.646); however, this estimate should be interpreted with caution, as it is based on only very limited studies with substantial between-study heterogeneity. Taken together, the findings suggest that communication in EFL extends beyond linguistic competence, encompassing interconnected psychological and intercultural processes. Nevertheless, the findings should be interpreted in light of the review’s methodological constraints, encompassing the exclusive use of the Scopus database and the restriction to open-access publications, which may have limited the coverage of relevant studies. Future studies are necessarily required to scrutinise these constructs within integrated theoretical frameworks and across more diverse educational and sociocultural contexts.